Case report: Cholecystoduodenostomy for cholestatic liver disease in a premature infant with cystic fibrosis and short gut syndrome - Laura K. Fawcett (BMC Pediatrics, 2019)
Abstract Background Cholecystoduodenostomy is a surgical procedure that bypasses the extrahepatic biliary tree and connects the gallbladder directly to the duodenum. This case describes the successful use of this procedure in a novel situation. Case presentation A premature (34 weeks gestation) female infant with cystic fibrosis required a laparotomy on day 1 of life due to an intrauterine small bowel perforation. Resection of small bowel and ileostomy formation resulted in short gut syndrome, with 82 cm residual small bowel and intact ileocaecal valve. Post-ileostomy reversal at 2 months old, she developed conjugated hyperbilirubinaemia. Despite conservative management including increased enteral feeding, ursodeoxycholic acid, cholecystostomy drain insertion and flushes, her cholestatic jaundice persisted. A liver biopsy revealed an “obstructive/cholestatic” picture with fibrosis. To avoid further shortening her gut with an hepatoportoenterostomy, cholecystoduodenostomy was performed at 3 months of age with subsequent post-operative improvement and eventual normalisation of her clinical jaundice and liver biochemistry. Conclusions This is the first reported case of a cholecystoduodenostomy being used successfully to treat an infant with persistent conjugated hyperbilirubinemia, cystic fibrosis and short gut syndrome. Cholecystoduodenostomy is a treatment option that with further study, may be considered for obstruction of the common bile duct in patients with short gut and/or where a shorter operating time with minimal intervention is preferred.